Quality of life of hemodialysis patients with anemia in Lombok, Indonesia - Candra Eka Puspitasari; Melda Putri Zakiah; Ni Luh Ayu Sri Widyasari; Ithnan Baqi Putra Erlangga; Kerthika Ayu Wandeni; Dinatul Aini; Sulthon Annaji; Widya Wulandari; Mahacita Andalusia; Yoga Dwi Saputra; Ni Made Amelia Ratnata Dewi (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2025)
Background: Anemia is a common complication of hemodialysis and is associated with substantial impairment of quality of life. Objective: This study evaluated the relationship between anemia biomarkers (hemoglobin and hematocrit) and health-related quality of life among patients receiving maintenance hemodialysis. Methods: A cross-sectional study was conducted at three hospitals on Lombok Island, Indonesia, involving 186 hemodialysis patients selected by purposive sampling. Quality of life was measured using the Indonesian-language KDQoL-SF36 questionnaire. Associations between hemoglobin, hematocrit, and quality-of-life scores were analyzed using Pearson's correlation and multiple linear regression (IBM SPSS version 29; p<0.05 considered significant). Results: The mean KDQoL-SF36 score was 63.60 ± 9.37. Age was significantly associated with quality of life (p = 0.024). Both hemoglobin and hematocrit showed significant positive correlations with quality of life (p<0.001), remaining significant predictors after multivariable adjustment. Conclusion: Hemoglobin and hematocrit levels are significant determinants of quality of life among hemodialysis patients. Optimizing anemia management, supported by active pharmacist involvement, may improve patient-reported outcomes in this population.